Kinetic study for compost production by isolated fungal strains - Kabbashi, Nassereldeen Ahmed; Opatakun, Suraj; Alam, Md Zahangir; Mirghani, Mohamed Elwathig Saeed (OMICS Group - Open Access Publisher, 2014)
Organic wastes, food wastes and trimming yard (FW and YT) were composted using selected fungal strains (Phanerochaete chrysosporium (PC), Lentinus tigrinus (LT), Aspergilus niger (ASP) and Penicillium Spp (PEN)) in a solid state bioconversion process. Results obtained at P ≤ 0.05 after ten harvests indicated the minimum value of germination index (GI) in the open system was 43 ± 105% while in the closed system it was 46 ± 132% respectively. The simplest zero and first order kinetic models described the microbial mineralization of carbon to nitrogen (C/N) relatively (R2 range of 0.87-0.99), but the second order model explained the observed kinetics of the solid state bioconversion (SSB) better with R2 range of 0.87–0.98 and a positive decay coefficient (k). The decay coefficient which indicates if all the components of the biomass decomposed at the same rate increases from -0.0584 to 2×10-4 for Phanerochaete chrysosporium stream & -0.0578 to 2×10-4 for Lentinus tigrinus stream in the open system across the zero, first and second order.